Calcium Oxalates in Lichens on Surface of Apatite-Nepheline Ore (Kola Peninsula, Russia) - Olga V. Frank-Kamenetskaya; Gregory Yu. Ivanyuk; Marina S. Zelenskaya; Alina R. Izatulina; Andrey O. Kalashnikov; Dmitry Yu. Vlasov; Evgeniya I. Polyanskaya (Minerals, 2019)
The present work contributes to the essential questions on calcium oxalate formation under the influence of lithobiont community organisms. We have discovered calcium oxalates in lichen thalli on surfaces of apatite-nepheline rocks of southeastern and southwestern titanite-apatite ore fields of the Khibiny peralkaline massif (Kola Peninsula, NW Russia) for the first time; investigated biofilm calcium oxalates with different methods (X-ray powder diffraction, scanning electron microscopy, and EDX analysis) and discussed morphogenetic patterns of its formation using results of model experiments. The influence of inorganic and organic components of the crystallization medium on the phase composition and morphology of oxalates has been analyzed. It was shown that, among the complex of factors controlling the patterns of biogenic oxalate formation, one of the main roles belongs to the metabolic activity of the lithobiont community organisms, which differs significantly from the activity of its individuals.